INCREASING INTEREST IN LEARNING ARABIC THROUGH THE APPLICATION OF THE NEARPOD APPLICATION FOR CLASS VIII STUDENTS OF SMPS MUHAMMADIYAH BATEBALLA KAB. BANTAENG - Khaeratul Mar’ah; Abd. Rahman; Nur Fadilah Amin (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The aim of this research is to determine the increase in students' interest in learning by using the Nearpod learning application in Arabic language learning in Class VIII SMPS Muhammadiyah Bateballa, Bantaeng Regency. This type of research is classroom action research which consists of two cycles where each cycle is carried out in one meeting. Research procedures include planning, observation, action implementation, and reflection. The data collection techniques used are observation, questionnaires and documentation. The research process data was analyzed using qualitative descriptive techniques, while the student questionnaire data were analyzed using quantitative descriptive techniques. From the results of the Classroom Action Research, it was concluded that the learning interest of class VIII students at SMPS Muhammadiyah Batebala in learning Arabic, there had been an increase in learning interest while implementing the nearpod learning application on each indikator. In cycle I, the percentage increase for the happy feeling indikator was 34.12%, the attention indikator was 34.73%, the interest indikator was 21.74%, and the acceptance indikator was 43.48%. Then the average value in Cycle I was 26.08 then increased in Cycle II to 60.86 with an average percentage increase of 34.78.